Titanium acetabular component deformation under cyclic loading - Beckmann, Nicholas A.; Bitsch, Rudi G.; Bormann, Therese; Braun, Steffen; Jäger, Sebastian (Materials, 2019)
Acetabular cup deformation may affect liner/cup congruency, clearance and/or osseointegration. It is unclear, whether deformation of the acetabular components occurs during load and to what extent. To evaluate this, revision multi-hole cups were implanted into six cadaver hemipelvises in two scenarios: without acetabular defect (ND); with a large acetabular defect (LD) that was treated with an augment. In the LD scenario, the cup and augment were attached to the bone and each other with screws. Subsequently, the implanted hemipelvises were loaded under a physiologic partial-weight-bearing modality. The deformation of the acetabular components was determined using a best-fit algorithm. The statistical evaluation involved repeated-measures ANOVA. The mean elastic distension of the ND cup was 292.9 µm (SD 12.2 µm); in the LD scenario, 43.7 µm (SD 11.2 µm); the mean maximal augment distension was 79.6 µm (SD 21.6 µm). A significant difference between the maximal distension of the cups in both scenarios was noted (F(1, 10) = 11.404; p = 0.007). No significant difference was noted between the compression of the ND and LD cups, nor between LD cups and LD augments. The LD cup displayed significantly lower elastic distension than the ND cup, most likely due to increased stiffness from the affixed augment and screw fixation.